Impact of osmoregulatory agents on the recovery of collagen conformation in decellularized corneas. (27th October 2016) - Murab, Sumit; Ghosh, Sourabh
Abstract: The process of decellularization of the cornea leads to the removal of cells and antigens. However, during decellularization the ultrastructure of the corneal matrix is usually damaged and a secondary conformation of the collagen fibrils is modulated resulting in altered transparency and physical properties. The strategy for recovering modulation in collagen conformation may help to attain the native physical properties and transparency of the cornea. Decellularized corneas were treated with varied concentrations of glycerol and dextran, and the collagen conformation was monitored by attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR), x-ray diffraction (XRD) and Raman spectroscopic analysis. The peak at 4 Å in XRD established the presence of transitional conformations that decreased with the application of osmoregulatory agents, but could not be completely eliminated. This was validated by the results of ATR-FTIR and Raman analysis. Importantly, the mechanism of this loss and the regaining of transparency has been proposed on the basis of the detachment of decorin molecules from the collagen triple helices, due to the change in collagen conformation during decellularization, and the subsequent partial reversal due to the desiccation effect of the osmoregulatory agents on collagen molecules. Taken together, collagen conformational transition can be considered as an indexing tool for the development of improved decellularization techniques.